Nuda szkolnego wychowania do życia w rodzinie - Buchnat, Marzena; Chmura-Rutkowska, Iwona; Gulczyńska, Anna (Studia Edukacyjne, 2018)
Despite a lot of scientific research and study, sexual education issues as an element of formal education are still considered to be a controversial subject. Those challenges, dilemmas, controversies or difficulties relate to many areas, connected both with form and organization of classes, teachers, and also (at more general level) with some ministerial indications or school management. All the above matters directly influence what sexual education classes look like and what the students’ experience is. It is disturbing that the sexual education subject at school was generally considered to be boring according to the respondents. Therefore, it has been decided to analyze why classes which are non-obligatory but important and wanted by students are considered boring and out of touch with life.